2005
DOI: 10.1002/pbc.20582
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic hypoglycemia: An unusual side effect of oral purine analogues for treatment of ALL

Abstract: Symptomatic hypoglycemia is an unusual complication in children receiving oral purine analogues for treatment of childhood acute lymphoblastic leukemia (ALL). The exact mechanism of the hypoglycemic effect of the antimetabolic therapy remains unclear. Reduced hepatic glycogen stores or impaired hepatic glyconeogenesis may partly explain the hypoglycemia. To prevent hypoglycemia, food containing complex carbohydrates is recommended before sleep. In severe cases of hypoglycemia due to 6-mercaptopurine (6-MP), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…Many publications identified hypoglycemia as an adverse but reversible side effect of MT for ALL that generally improves 3–4 months after completion of therapy but could not identify why it occurred . Our patients had symptomatic hypoglycemia associated with 6‐MP therapy similar to that found by other investigators.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Many publications identified hypoglycemia as an adverse but reversible side effect of MT for ALL that generally improves 3–4 months after completion of therapy but could not identify why it occurred . Our patients had symptomatic hypoglycemia associated with 6‐MP therapy similar to that found by other investigators.…”
Section: Discussionsupporting
confidence: 70%
“…The symptoms for hypoglycemia, defined as a blood glucose level less than 50 mg/dl, include nausea, fatigue, headache, irritability, and dizziness. Bay et al described a 3‐year‐old male who developed fasting hypoglycemia during MT in association with elevated alanine aminotransferase (ALT) . They showed improvement with the addition of complex carbohydrates in the evening, a switch from evening to morning 6‐MP dose administration, and a 6‐MP dose reduction.…”
Section: Introductionmentioning
confidence: 99%
“…1 In a case, the patient could not adapt himself to such regime and the number of severe hypoglycemic attacks continued that necessitated discontinuing 6-MP. 3 In a study of nocturnal hypoglycemic seizures, hypoglycemia less than 60 mg/dL was reported to last 2.25 to 4 hours before seizures occur. 5 This can further contribute to hypoglycemic brain injury with irreversible effects if the hypoglycemia is severe or prolonged enough.…”
Section: Discussionmentioning
confidence: 98%
“…Hypoglycemia may also be due to increased glucose consumption by the tumor [28]. Iatrogenic hypoglycemia has also been reported in patients treated with rituximab [29], tyrosine kinase inhibitors [30], and oral purine analogues [31], as well as in those receiving trimethoprim/sulfamethoxazole [32]; all these drugs are commonly used in the allogeneic HCT setting. A suggested mechanism for antibiotic-associated hypoglycemia is the sulfonylurea-like effect [32].…”
Section: Hypoglycemiamentioning
confidence: 99%